Parallel mechanochemical optimization – Buchwald–Hartwig C–N coupling as a test case. Issue 14 (29th June 2022) - Lemesre, Quentin; Wiesner, Thomas; Wiechert, Rainer; Rodrigo, Eduardo; Triebel, Sonja; Geneste, Hervé
Abstract : Reaction conditions for mechanochemical Ar-amination were optimized in parallel: in a maximum of four steps [neat, LAG (water or methanol) and AG (sand) conditions] the yield could be significantly improved. The reaction time is short, and the conversion and purity are high. Abstract : Buchwald–Hartwig aromatic amination has been chosen as a test case for reaction condition optimization in a mechanochemical setting. A parallel approach has allowed a fast investigation of different parameters. In particular, liquid-assisted grinding (LAG) as well as addition of a grinding auxiliary (AG) proved to significantly increase the yield. Key learnings are the high reproducibility and the reliability of the NMR-yield as a surrogate for the isolated yield. Moreover the catalytic system (Pd(OAc)2 in combination with t BuXPhosPdG3) compares favorably to previously published catalytic systems.